The Effect of Guided Inquiry Learning Model on Students Learning Outcomes in Mathematics Education - Satriawan, M. Agus (YASIN, 2025)
Education plays an important role in creating social order and improving the quality of human resources. This study aims to analyze the effect of guided inquiry learning models on students' mastery of concepts in mathematics learning. The method used is a quantitative experiment with a non-equivalent control group design. The research sample consisted of two groups, namely the experimental group using the guided inquiry learning model and the control group using conventional methods. Data were obtained through pretest and posttest, with validity, reliability, and t-test analysis to test the hypothesis. The results showed that there was a significant difference in concept mastery between the experimental and control groups, with average values ​​of 84 and 72.33, respectively. The t-test results showed tcount = 3.957> ttable = 2.012, so the hypothesis was accepted. The biserial correlation coefficient of 0.650 indicates a strong influence, and the determination coefficient of 42.30% indicates that the guided inquiry learning model contributes to improving student learning outcomes. Thus, this model is recommended as an alternative learning method in improving students' understanding of concepts.